Z-score mapping for standardized analysis and reporting of cardiovascular magnetic resonance modified Look-Locker inversion recovery (MOLLI) T1 data: Normal behavior and validation in patients with amyloidosis - Kranzusch, Riccardo; Siepen, Fabian aus dem; Wiesemann, Stephanie; Zange, Leonora; Jeuthe, Sarah; Ferreira da Silva, Tiago; Kuehne, Titus; Pieske, Burkert; Tillmanns, Christoph; Friedrich, Matthias; Schulz-Menger, Jeanette; Messroghli, Daniel R. (Journal of cardiovascular magnetic resonance, 2020)
T1 mapping using modified Look-Locker inversion recovery (MOLLI) provides quantitative information on myocardial tissue composition. T1 results differ between sites due to variations in hardware and software equipment, limiting the comparability of results. The aim was to test if Z-scores can be used to compare the results of MOLLI T1 mapping from different cardiovascular magnetic resonance (CMR) platforms.
Gesehen am 02.04.2020